Degradation of phenanthrene and pyrene using genetically engineered dioxygenase producing Pseudomonas putida in soil - Mardani Gashtasb (Genetika, 2016)
Bioremediation use to promote degradation and/or removal of contaminants into nonhazardous or less-hazardous substances from the environment using microbial metabolic ability. Pseudomonas spp. is one of saprotrophic soil bacterium and can be used for biodegradation of polycyclic aromatic hydrocarbons (PAHs) but this activity in most species is weak. Phenanthrene and pyrene could associate with a risk of human cancer development in exposed individuals. The aim of the present study was application of genetically engineered P. putida that produce dioxygenase for degradation of phenanthrene and pyrene in spiked soil using high-performance liquid chromatography (HPLC) method. The nahH gene that encoded catechol 2,3-dioxygenase (C23O) was cloned into pUC18 and pUC18-nahH recombinant vector was generated and transformed into wild P. putida, successfully. The genetically modified and wild types of P. putida were inoculated in soil and pilot plan was prepared. Finally, degradation of phenanthrene and pyrene by this bacterium in spiked soil were evaluated using HPLC measurement technique. The results were showed elimination of these PAH compounds in spiked soil by engineered P. putida comparing to dishes containing natural soil with normal microbial flora and inoculated autoclaved soil by wild type of P. putida were statistically significant (p<0.05). Although adding N and P chemical nutrients on degradation ability of phenanthrene and pyrene by engineered P. putida in soil were not statistically significant (p>0.05) but it was few impact on this process (more than 2%). Additional and verification tests including catalase, oxidase and PCR on isolated bacteria from spiked soil were indicated that engineered P. putida was alive and functional as well as it can affect on phenanthrene and pyrene degradation via nahH gene producing. These findings indicated that genetically engineered P. putida generated in this work via producing C23O enzyme can useful and practical for biodegradation of phenanthrene and pyrene as well as petroleum compounds in polluted environments.